Herlyn-Werner-Wunderlich Syndrome: A Case Report - Deepak Lamichhane; Anshu Sutihar; Gubeanthrey Janakyraman; Rudish Jaz Shrestha; Mahbubur Rahman Razeeb (Journal of Nepal Medical Association, 2023)
Herlyn-Werner-Wunderlich syndrome is a rare congenital malformation of the Mullerian ducts characterized by uterine didelphys with obstructed hemivagina and ipsilateral renal agenesis. Commonly, such patients present with pelvic pain, dysmenorrhea following menarche, and an abdominal mass secondary to hematometrocolpos. In this report, a case of a 14-year-old female presented with abdominal pain, back pain and acute urinary retention. She attained menarche at the age of 10 years; however, symptoms of dysmenorrhea only appeared 4 years later. She was eventually diagnosed with the help of ultrasound and computed tomography urogram. She was managed conservatively with an incision and drainage procedure and was also advised for resection of vaginal septum. The nonspecific nature of symptoms such as regular menstruation with cyclical abdominal pain impedes the diagnosis which can lead to an array of complications. Awareness of this syndrome can help avoid misdiagnosis and allow for early surgical intervention.